SANKSI TERHADAP KORPORASI SEBAGAI PENYELENGGARA SISTEM ELEKTRONIK AKIBAT KEBOCORAN DAN PENYALAHGUNAAN DATA PRIBADI - Ornella Angelia, Rina Rahma; Erwin, Rahmi; Desmon, Andi (Ensiklopedia of Journal, 2024)
This research focuses on imposing sanctions on Corporations as Electronic System Operators (PSE) if the Corporation fails to carry out its obligations and misuses User's Personal Data improperly based on Law Number 27 of 2022 concerning Protection of Personal Data. The method used in this research is normative-descriptive legal research and normative-juridical research. Normative Descriptive is research that aims to find correlation, which relates to legal rules in accordance with legal norms and whether there are legal norms in the form of orders and prohibitions that are in accordance with legal principles and whether there are actions (acts) in accordance with legal norms and legal principles. Normative Juridical, namely conducting research with an approach, examining, concepts, and related theories to study existing regulations to obtain answers to legal issues in this writing. This type of research is research on legal systematics by conducting research that has the aim of identifying the understanding and legal basis that exists. The results of this study indicate that in Law No. 27 of 2022 concerning Protection of Personal Data there are strict sanctions for Corporations as Electronic System Operators (PSE) if the Corporation leaks or misuses its Users' Personal Data.Keywords: Personal Data, Corporations, Sanctions.